VACATIO LEGIS IN TAX LAW - Medelienė, Aistė; Lukas, Mindaugas (Teisė, 2015)
This article analyses the content and application of principle of vacatio legis in the field of taxation. Taxes, being one of the most important elements of every state, undoubtedly are one of the essential factors of the political society as well. Therefore it is crucially important to ensure that taxes are established and changed only by the procedure strictly in line with the constitutional principles of legal expectations and legal security. Vacatio legis means that there should be a gap between the enactment and announcement of the law and it’s coming into force / beginning of its application. This rule ensures that persons have the opportunity to properly prepare for the application of new legislation. Vacatio legis and lex retro non agit ensure the confidence of taxpayers in the state and protects their legal expectations. Accordingly they could be defended invoking the Constitution. Legal acts of Lithuania (Law on Tax Administration and Law on the Fundamentals of Legislation) establish that tax laws enacting a new tax, setting new tax rate, introducing tax relief and/or sanctions for violations of the tax laws or substantially amending the procedure of specific taxation or the principles of the legal regulation of taxation will come into effect no earlier than in six months after the day of their publication. This term once again affirms the importance of tax rules in the political society. The abovementioned requirement has two exemptions and one of them could be applied when tax laws are directly related and enacted together with the law on next year‘s national budget (Law on the Approval of Financial Indicators of the State Budget and Municipal Budgets). This exemption was widely used by the legislator enacting the amendments of tax laws in Lithuania during the economic crisis. Unfortunately it is used for changing of subsequent tax laws as well. Although the Constitutional Court in its doctrine acknowledged that the amendments of tax laws, made during the economic crisis, which were enacted ignoring vacatio legis, are not in conflict with the Constitution as they were made in the extraordinary situation of economic crisis in the state, however it should be pointed out that the Constitutional Court also stressed that using of the exemptions of vacatio legis should be more the exception than a rule and used only in the exclusive circumstances having the very strong reasons for that.